Role of Participation of Pediatricians in the "Activated Autism Practice" Program in Practicing Children With Autism Spectrum Disorders at the Primary Care Setting - Steven W. Kairys MD, MPH; Anna Petrova MD, PhD, MPH (SAGE Publishing, 2016)
Primary care of children with autism spectrum disorders (ASD) is an important public health concerns. In this survey study of 73 pediatricians, we determined whether pediatricians' practice of autism screening and perception of management of ASD is associated with participation in a learning collaborative, "Activated Autism Practice". Overall, the majority recognized the lack of care coordination, inadequate time, poor reimbursement, and language difference as barriers to the delivery of medical care to children with ASD. Pediatricians with prior training were more likely to report use of autism-specific screening and understanding the different aspects of ASD management including the need to coordinate special services and long-term surveillance at pediatric sites. Therefore, participation in "Activated Autism Practice" may facilitate use of ASD-specific screening and manage ASD cases as a complex of neurodevelopmental/underlying problems with the need for enhancement of clinical attention and coordination of medical care at the pediatric primary care level.